(Blue) Growth accounting in small-scale European Union fleets. (February 2019) - Da-Rocha, José-María; Guillen, Jordi; Prellezo, Raúl
Abstract: Fisheries account for one-third of the total jobs in the world's ocean economies. In the European Union (EU), small-scale fleets account for over 40 % of employment in the fisheries sector. Given this marine employment source, it is important to analyse SSF productivity growth. This is done here using Total Factor Productivity (TFP), defined as the portion of output not explained by the traditionally measured inputs of labour, energy and capital used in production. Calculating TFP is relevant to understanding the development of technology in fisheries. It is calculated for SSF in two main EU sea areas: the Mediterranean (FAO area 37) and the North-East Atlantic (FAO area 27). Constant elasticity production functions are used to analyse the intensity of the use of production factors and how they are substituted or complemented when producing. Additionally, TFP is corrected by stock evolution indices to assess EU conservation policy. The results show that there is complementarity between capital and energy and external factors affecting them and that the productivity increase observed in the Atlantic can be attributed mainly to stock recovery and resource availability rather than to production factors. This suggests that technological development has been limited and that the use of production factors should be decreased in the coming years. It is concluded that in the North-East Atlantic the EU conservation policy is fulfilling the objective of restoring fish stocks and contributing to a productivity growth of 4 % per year. In the Mediterranean, stocks are not being restored, so they do not contribute to growth as a production factor. Finally, it is concluded that the conservation policy does not suffice in either area to provide positive productivity trends. Abstract : Highlights: Small scale fleets are a mayor contributor to labour in the EU marine sectors. Small scale fleet's productivity grows a 4% per year in the Atlantic mainly due to the recovery of the stocks. Productivity growth is stagnated in the Mediterranean. Additional policies beyond the conservation of stocks are required to boost small scale fleet's productivity.